(untitled) (Research, Society and Development, 2021)
Sugarcane is one of the main crops explored in Brazil, whether under rainfed or irrigated conditions. Water and the nutrient potassium are inputs that can interfere with the physiology of this crop and, when supplied in fertigation, allows for greater efficiency in the use of water and fertilizers. Potassium is the nutrient most required by sugarcane and its efficiency is improved when fertigation is used. Thus, the objective was to evaluate the physiological responses of sugarcane during the third cropping cycle (stump) regarding the application of potassium doses under rainfed and irrigation conditions. The experiment was carried out in a split-plot scheme (4 x 2), with four doses of potassium fertilization (0, 70, 140 and 210 kg ha-1 of K2O) with and without irrigation. The stomatal conductance was higher when the sugarcane plants were irrigated at all doses of potassium studied, except for the control at 235 and 393 days after cutting. The SPAD index showed no difference between irrigated and dryland conditions in all doses of potassium fertilization and evaluation periods. There is a difference in the leaf area index between irrigated plants and under rainfed conditions only when the dose of 140 kg ha-1 of K2O is applied 340 days after cutting.